A discrete wavelet transform-based audio watermarking technique for digital security. (30th June 2022) - Prabhu, V.; Sundar, Laxmi; Drishya, V.; Rajeshwari, G. Ruby Alice; Thomas, D. Ruban
This work proposes a model using discrete wavelet transform (DWT) to eliminate the attacks on digital security. Semi-fragile watermarking techniques strive towards establishing the confidentiality of data content. Minutiae algorithm finds its application in various fields to safeguard and protect the data content ensuring integrity of data security, authenticity, copyright proofs and data ownership. This work is based on the usage of the combined technique of employing the minutiae algorithm along with DWT for the secured retrieval of audio data to protect network security. Experimental results are shown for the proposed technique based on minutiae algorithm and DWT by considering the four parameters - signal-to-noise ratio (SNR), computation time, entropy and IQI. DWT ensures high secured digital network in areas like defense, satellite and related fields.